2003
DOI: 10.1007/s00125-002-1011-6
|View full text |Cite
|
Sign up to set email alerts
|

Loss of beta-cell mass leads to a reduction of pulse mass with normal periodicity, regularity and entrainment of pulsatile insulin secretion in G�ttingen minipigs

Abstract: Aims/hypothesis. Type 2 diabetes is associated with impaired insulin action and secretion, including disturbed pulsatile release. Impaired pulsatility has been related to impaired insulin action, thus providing a possible link between release and action of insulin. Furthermore, progressive loss of beta-cell mass has been implicated in the pathogenesis of Type 2 diabetes. The aim of this study was to evaluate a possible link between loss of beta-cell mass and impaired pulsatile insulin secretion with special fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…In humans normal fasting plasma glucose levels are below 5.6 mmol/L, impaired plasma glucose levels are between 5.6 and 7 mmol/L, while type 2 diabetes has plasma glucose levels above 7 mmol/L. Previous research indicated lower fasting plasma glucose levels for the minipig (i.e., 3.6 mmol/L Larsen et al, 2003), whereas the domestic pig is estimated at the same level as humans (Larsen and Rolin, 2004). In our resource population, FGLs range between 1.80 and 11.15, with an average of 4.50 (SE = 2.18).…”
Section: Resultsmentioning
confidence: 96%
“…In humans normal fasting plasma glucose levels are below 5.6 mmol/L, impaired plasma glucose levels are between 5.6 and 7 mmol/L, while type 2 diabetes has plasma glucose levels above 7 mmol/L. Previous research indicated lower fasting plasma glucose levels for the minipig (i.e., 3.6 mmol/L Larsen et al, 2003), whereas the domestic pig is estimated at the same level as humans (Larsen and Rolin, 2004). In our resource population, FGLs range between 1.80 and 11.15, with an average of 4.50 (SE = 2.18).…”
Section: Resultsmentioning
confidence: 96%
“…Η ελάττωση του αριθμού των β-κυττάρων στο ΣΔ δε φαίνεται να την εξηγεί. Έχει δειχθεί ότι η καταστροφή των β-κυττάρων οδηγεί σε ελάττωση του εύρους των ώσεων, χωρίς επίδραση στη συχνότητα [207] [208], ούτε στο συντονισμό με τη γλυκόζη [209]. Πιθανότατα οφείλεται σε μία διαταραχή οποιουδήποτε από τα πολυάριθμα μοριακά βήματα που μεσολαβούν μεταξύ της πρόσληψης και της μεταφοράς της γλυκόζης στο β-κύτταρο και της εξωκύτωσης των κοκκίων της ινσουλίνης (σύζευξη ερεθίσματοςέκκρισης-stimulus-secretion coupling).…”
Section: οι ώσεις της ινσουλίνης στο διαβήτηunclassified